Influence of melt treatment parameters on the characteristics of modified cast iron in the metallurgical industry using intellectual analysis methods - Boldyrev, Denis; Dema, Roman; Latypov, Oleg; Zhilenkov, Anton; Emelianov, Vitalii; Nedelkin, Alexey (Eastern-European Journal of Enterprise Technologies, 2021)
A study of the effect of holding the cast iron melt at temperatures of 1,300, 1,450 and 1,600 °C for 20, 55 and 90 minutes on the structure and properties of cast iron in a liquid state and after crystallization was carried out. The studies were carried out on samples with a diameter of 30 mm; cast iron containing 3.61–3.75 % carbon, 1.9–2.4 % silicon, 0.03 % manganese, 0.081–0.084 % phosphorus, 0.031–0.039 % sulfur was poured into green-sand molds. The samples were cast from the original cast iron (unmodified), modified with ferrosilicon 75 GOST 1415-93 (FS75), rare-earth metals (REM) and together with the REM+FS75 complex. The structure of cast iron was investigated by optical metallography, electron microscopy and X-ray structural analysis. An increase in the holding temperature and time of the cast iron melt leads to an increase in its hardness. An increase in temperature at a short holding time leads to an increase in strength in the entire investigated temperature range (1,300–1,600 °С). Holding for 90 minutes at a temperature of 1,450 °C corresponds to an extremum, after which, with a further increase in temperature, a sharp drop in strength is observed. The change in the toughness of cast iron is characterized in a similar way